Assess the quality of air Basra province - اسراء عادل رسول (College of Education for Women, 2019)
Iraqi provinces suffer many of the environmental problems, appear explained these problems in the city of Basra, Basra, the largest province and is among Iraq's provinces in the annexation of oil fields, which is experiencing an oil production operations of large, it suffers from the burning of gas associated with oil extraction resulting in the emission severe gas process including toxic hydrogen sulfide gas (h2S) and oxides of carbon, sulfur and nitrogen in addition to the release of toxic metal elements such as mercury, arsenic, vanadium, which caused the man many serious diseases. , And perhaps one of the most important of these problems are worsening air quality and increasing cases of air pollution and the deterioration of the quality of facilities in the industrial and cultural development. The research aims to study assessing the quality of air Basra province through the concentrations of pollutants solid air which include total suspended minutes Total Suspended Particles (TSP measure) and lead (pb), through the analysis of the results (40) model daily to measure the total outstanding minutes and analysis (30 model) daily to measure the concentrations of lead in the air at one station in Basra Directorate of Environment building in the center of the province in 2007.Search Results showed that there is a rise in the concentration of the outstanding minutes where they were recording the lowest and highest daily concentration reaching (67) and (3597) ug / m3 for the months (July and December) and April respectively. Also found a significant increase in the concentrations of the daily outstanding minutes annual rate, as it exceeded the permissible limits by comparing it with the local and global determinants the (350) and (150) ug / m3 respectively. We conclude from this that air Basra province contaminated minutes outstanding is due to the influence of fly dust because most of the sites are influenced by dust fly by dust storms and operations of drilling oil wells, as well as the effect of divorced exhaust generators and transportation and some industrial activities). Search results showed that the measurement of the concentration of lead did not exceed the standard parameters allowed locally and globally to air pollutants and Albalgth (2 micrograms / m3 on a daily basis) and (1.5 ug / m3 on average per year), respectively, with the exception of the highest concentration was recorded, a (3.5) microg / m3 in the month of May is the only measurement that exceeded the proposed national specified for the lead during the measurement period. We conclude from this study that the pollutants solid aerodynamic effects harmful to the environment and health.